2011
DOI: 10.2166/wst.2011.139
|View full text |Cite
|
Sign up to set email alerts
|

Fouling with aerobic granule membrane bioreactor

Abstract: Aerobic granulation (AG) and membrane bioreactor (MBR) are two promising, novel environmental biotechnological processes that draw interest of researchers working in the area of biological wastewater treatment. Membrane fouling in the combined aerobic granular membrane bioreactor (AGMBR) process and the conventional MBR process was investigated in this work. The irreversible fouling on hollow-fibre membranes in both reactors were observed with the multiple staining and confocal laser scanning microscope techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The presence of both hydrophobic and hydrophilic groups in EPS implies that they are amphoteric in nature. Since the hydrophilic fraction is known to foul the membrane (hydrophilic membrane) more than the hydrophobic fraction, the proportion of hydrophobic to hydrophilic organics plays an important role in the formation of fouling [ 105 ]. Thus, the ratio of proteins (hydrophobic) to polysaccharides (hydrophilic) in EPS governs membrane fouling in MBRs, especially cake layer formation [ 12 ].…”
Section: Factors Affecting Membrane Fouling In Mbrmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of both hydrophobic and hydrophilic groups in EPS implies that they are amphoteric in nature. Since the hydrophilic fraction is known to foul the membrane (hydrophilic membrane) more than the hydrophobic fraction, the proportion of hydrophobic to hydrophilic organics plays an important role in the formation of fouling [ 105 ]. Thus, the ratio of proteins (hydrophobic) to polysaccharides (hydrophilic) in EPS governs membrane fouling in MBRs, especially cake layer formation [ 12 ].…”
Section: Factors Affecting Membrane Fouling In Mbrmentioning
confidence: 99%
“…Another study by Juang et al [ 105 ] investigated membrane fouling in AGMBR and reported that most bacteria cells were retained by the granules thus preventing their penetration through the membrane pores and the chance to cause internal fouling layer. The combination of aerobic granulation and MBR has also been reported to enhance good filtration performance and lower propensity for membrane fouling [ 115 ].…”
Section: Current Research Trends For Membrane Fouling Abatement Inmentioning
confidence: 99%